3D printing of shape memory poly(d, l‐lactide‐co‐trimethylene carbonate) by direct ink writing for shape‐changing structures. Issue 44 (28th June 2019) - Wan, Xue; Wei, Hongqiu; Zhang, Fenghua; Liu, Yanju; Leng, Jinsong
ABSTRACT: Four‐dimensional (4D) printing of shape memory materials has attracted increasing interests for personalized structures. In this study, a biocompatible poly(d, l ‐lactide‐ co ‐trimethylene carbonate) (PLMC) is utilized to fabricate 4D shape‐changing structures with customized geometries through direct ink writing. The printed objects show shape transformations at different dimensions under thermal programming. The influence of the printing parameters on the properties including rheological, solvent evaporation, and static mechanical behavior are systematically investigated. A printing map is further depicted to achieve high‐quality printing with high viscous ink flowed from micronozzle to construct various structures. The printed structures in one‐dimensional, two‐dimensional, and three‐dimensional (3D) exhibit shape‐changing behavior with fast response around body temperature. The fast responsive time shows potential in the field of surgical suture (4 s), nonwoven fabric (3 s), and self‐expandable stent (35 s). The feasibility of 3D printing of PLMC opens the way for applications in shape‐changing devices with small diameter. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48177. Abstract : 3D printing of poly(D, L‐lactide‐co‐trimethylene carbonate) for shape changing structures